Conceptual design of AM components using layout and geometry optimization. (1st October 2019) - He, Linwei; Gilbert, Matthew; Johnson, Thomas; Pritchard, Tom
Abstract: In this paper truss layout optimization is used in conjunction with geometry optimization to provide the basis for a powerful conceptual design tool for additively manufactured (AM) components, particularly useful when the degree of design freedom is high. With layout optimization the design domain is discretized using a grid of nodes which are interconnected with discrete line elements, forming a 'ground structure'. Linear optimization can then be used to identify the subset of elements forming the minimum volume structure required to carry the applied loading. A nonlinear geometry optimization step, which involves adjusting the positions of the nodes, can subsequently be undertaken to simplify and improve the solution. Simple geometrical rules can then be used to automatically transform a line element layout into a 3D continuum, ready for validation and/or manufacture. Various extensions to the basic method are described in the paper, including AM build direction constraints and techniques to permit user-interaction with candidate designs, which has been found to be invaluable at the conceptual design stage. Finally the approach described is applied to a range of design problems, including the redesign of an airbrake hinge for the Bloodhound Supersonic Car.